2007
DOI: 10.1074/jbc.m607910200
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of a Human Cell Line from Endogenous Cdk1 Depletion by Cdk1 Lacking Inhibitory Phosphorylation Sites

Abstract: Cells that transiently overexpress cyclin-dependent kinase 1 lacking inhibitory phosphorylation sites (Cdk1-AF) undergo premature and catastrophic mitosis, reflecting the key role for Cdk1 in promoting a timely transit from G 2 into mitosis. Conversely, cells depleted of Cdk1 undergo repeated S phases without intervening mitoses (endoreduplication), reflecting a role for Cdk1 in preventing premature S phases. It is not known how Cdk1 prevents entry into S phase at times in G 2 when it does not promote mitosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
2
10
2
Order By: Relevance
“…Also consistent with the model in Fig. 2C is the ability of Cdk1 that lacks inhibitory phosphorylation sites, and is therefore unresponsive to Cdc25 phosphatase, to prevent endoreduplication in HT2-19 without promoting mitosis [ 37 ].…”
Section: Introductionsupporting
confidence: 72%
“…Also consistent with the model in Fig. 2C is the ability of Cdk1 that lacks inhibitory phosphorylation sites, and is therefore unresponsive to Cdc25 phosphatase, to prevent endoreduplication in HT2-19 without promoting mitosis [ 37 ].…”
Section: Introductionsupporting
confidence: 72%
“…Only weak USP22 phosphorylation was detected in HCT116 cells, presumably catalyzed by endogenous CDK1, and CDK1 overexpression significantly increased USP22 phosphorylation. In addition, expression of the constitutively active form of CDK1 (CDK1/AF) [ 37 , 38 ] further enhanced USP22 phosphorylation in HCT116 cells ( Figure 4b ). Moreover, mutation of the aspartic acid at position 146 of CDK1 (CDK1/D146N), which is a kinase-inactive mutant [ 39 ], completely abolished its ability to promote USP22 phosphorylation ( Figure 4b ).…”
Section: Resultsmentioning
confidence: 99%
“…However, several subsequent studies showed that although the introduction of CDK1AF does result in premature activation of CDK1 in HeLa cells, it has little or no effect on the timing of chromatin condensation and nuclear envelope breakdown (NEB) (Jin et al, 1996(Jin et al, , 1998Blasina et al, 1997). Moreover, one recent study has shown that human HT2-19 cells can be obtained that both tolerate and require CDK1AF for growth and division (Gupta et al, 2007). These results indicate that the inhibitory phosphorylation of CDK1, and the positive feedback loops that depend upon this inhibitory phosphorylation, are not essential for normal mitotic timing in HeLa cells and not essential for viability in HT2-19 cells.…”
mentioning
confidence: 99%